Assessment of Depression and Anxiety Among Adult Patients With Solid Tumours Admitted in National Institute of Cancer Research & Hospital - Ayub, Salman Bashar Al; Rahman, Mohammad Habibur; Islam, Muhammad Rafiqul; Khatun, Nazrina (Bangladesh Journal of Medicine, 2023)
Background: Cancer is one of the most common causes of mortality & morbidity globally, accounting for an estimated 10 million deaths in 2020. The diagnosis of cancer is a stressful event causing significant psychological distresses, most commonly depression and anxiety, directly interfering with disease outcome and quality of life. The aim of the study is to assess the level of depression and anxiety among adult patients with solid tumours as well as the association of various socio-demographic and clinical factors with them. Methods: This cross-sectional type of descriptive study was conducted at the National Institute of Cancer Research & Hospital (NICRH), Dhaka for a period of 12 months. A total of 405 histologically confirmed adult solid tumour patients were enrolled in the study using purposive sampling after fulfilling inclusion and exclusion criteria. Data were collected from the patients by face-to-face interviews using a semi-structured questionnaire and Bangla version of the DASS-21 scale. Results: In this study, the mean age of the respondents was 47.4 ± 16.5 years, the respondents were predominantly male with the male-tofemale ratio being 3:2 roughly. Gastrointestinal cancers (27.4%) were most prevalent, followed by lung (19.5%), gynaecological (11.4%), breast cancers and sarcomas (both 9.4%). The majority of the patients were undergoing chemotherapy (71.9%) and harbouring stage IV disease (64.4%) with duration of illness for less than twelve months (62% of respondents). The prevalence of depressive and anxious symptomatology among all patients was 38.02% and 42.96%, respectively. More than half (53.3%) of the adult patients with solid tumours were suffering from either of depression and/or anxiety. 19.7% had mild, 13.6% had moderate, 3.7% had severe and 1% had extremely severe levels of depression, while the percentages were 17.3%, 11.6%, 9.4% and 4.7% respectively, for severity of anxiety. In inpatient setting, depressive disorders were significantly higher in females than males (p<0.01) and among the lung cancer patients; in contrast, gastrointestinal cancer and the presence of co-morbidities predisposed more to anxiety (p<0.05). Although mode of treatment and severity of disease showed no significant relationship with the prevalence of depression or anxiety, ECOG performance status was found to have a significant impact on both of the disorders. On analysis of the socio-demographic variables, illiterate and low-income people were seen to suffer more with a severe and extremely severe level of depression, on the other hand, homemakers and lower socio-economic class had higher levels of anxiety. Conclusion: The study findings demonstrated a higher prevalence of depressive and anxious symptomatology in the inpatient setting; therefore, counselling, screening, and timely evaluation of mental health should be a part of the standard protocol of oncology care. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 215-216